Time-Course Transcriptome Analysis of Compatible and Incompatible Pollen-Stigma Interactions in Brassica napus L. - Zhang, Tong; Gao, Changbin; Yue, Yao; Liu, Zhiquan; Ma, Chaozhi; Zhou, Guilong; Yang, Yong; Duan, Zhiqiang; Li, Bing; Wen, Jing; Yi, Bin; Shen, Jinxiong; et al. (Frontiers in Plant Science, 2017)
Brassica species exhibit both compatible and incompatible pollen-stigma interactions, however, the underlying molecular mechanisms remain largely unknown. Here, RNA-seq technology was applied in a comprehensive time-course experiment (2, 5, 10, 20 and 30 min) to explore gene expression during compatible/incompatible pollen-stigma interactions in stigma. Moderate changes of gene expression were observed both in compatible pollination (PC) and incompatible pollination (PI) within 10 minutes, whereas drastic changes showed up by 30 minutes, especially in PI. Stage specific DEGs (Differentially Expressed Gene(s)) were identified, and signaling pathways such as stress response, defense response, cell wall modification and others were found to be over-represented. In addition, enriched genes in all samples were analyzed as well, 293 most highly expressed genes were identified and annotated. Gene Ontology and metabolic pathway analysis revealed 10 most highly expressed genes and 37 activated metabolic pathways. According to the data, downstream components were activated in signaling pathways of both compatible and incompatible responses, and incompatible response had more complicated signal transduction networks. This study provides more detailed molecular information at different time points after compatible and incompatible pollination, deepening our knowledge about pollen-stigma interactions.